Identifikasi Nematoda di Lahan Perkebunan Buah Naga (Hylocereus costaricencis) Kabupaten Banjar dan Banjarbaru Kalimantan Selatan - Reny Adhani; Dewi Fitriyanti; Abdul Gafur (Bioscientiae, 2017)
Dragon Fruit is one of the important crop plants in South Borneo. Efforts to increase production are sometimes inhibited by pathogenic nematodes. The aim of this study is to identify and describe the nematodes found in the soil around the dragon fruit farmland in Banjar and Banjarbaru districts. Research was done by taking the soil at a depth of 0-20 cm near the roots of the dragon fruit. The nematode extraction was done with Whitehead & Heaming method (1965) and fixed by Seinhorst method (1962), then proceed with mounting method Seinhorst (1959). Furthermore, morphological observations consisted of the entire body from head to tail. Nematodes that have been identified on the Dragon Fruit farmland are the genera Pratylenchus, Rotylenchus, Tylenchorhynchus, Mylonchulus, Eudorylaimus and Nygolaimoides. The identified nematodes may serve as additional information about the nematodes present in the dragon fruit farmland.